Informationsflödet mellan kund och Göteborgs Energihamn innan och under anlöp - Fallstudie av den information som behövs för att möjliggöra effektivisering av anlöp i Göteborgs Energihamn - Calizaya Arce, Emil; Vesterelve, Josefine (My University, 2017)
In recent years, the definition of customer value has changed and today customers themselves decide when a customer value has been created. Therefore, companies must interact and engage with their customers in a way they previously did not have to, and instead treat every customer relationship as unique and one which needs a constant evaluation. For this reason, Port of Gothenburg wanted to investigate the information flow between the Energy Port and its customers, which, in this study, refers to terminals and ship agents, in connection to a port call. This resulted in a case study which aimed to investigate the mentioned information flow, how everyone involved perceives it and what other information is needed to improve their work efficiency. Semi-structured interviews were carried out to answer the questions in issue; the respondents were chosen carefully to achieve as valid result as possible. The result shows that the information flow, at the moment, is structured in the way of a decentralized network. This is perceived by the parties as a semi-working solution, as they see there is a need for more defined areas of responsibility, as well as better communication regarding what information each actor actually needs from the other parties. The conclusion from this study shows that the best way to streamline the information flow would be to restructure the network from a decentralized to a centralized network.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics